2019
DOI: 10.1097/sla.0000000000003274
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Patient-controlled Analgesia Compared With Epidural Analgesia After Open Hepatic Resection

Abstract: Objective: To compare the efficacy and safety of patient-controlled analgesia (PCA) to epidural analgesia in adults undergoing open hepatic resection. Background: Effective pain management in patients undergoing open hepatic resection is often achieved with epidural analgesia. However, associated risks have prompted investigation of alternative analgesic methods in this patient population. Methods: A compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Five RCTs [35][36][37][38][39] and one meta-analysis 40 compared the analgesic effect of TEA with opioid intravenous PCA. The meta-analysis that included four RCTs (n=278 patients) demonstrated that, compared with opioid intravenous PCA, TEA provided superior pain relief at rest and with movement at 12 and 24 hours after surgery, with no significant difference in hospital length of stay (LOS).…”
Section: Thoracic Epidural Analgesiamentioning
confidence: 99%
See 2 more Smart Citations
“…Five RCTs [35][36][37][38][39] and one meta-analysis 40 compared the analgesic effect of TEA with opioid intravenous PCA. The meta-analysis that included four RCTs (n=278 patients) demonstrated that, compared with opioid intravenous PCA, TEA provided superior pain relief at rest and with movement at 12 and 24 hours after surgery, with no significant difference in hospital length of stay (LOS).…”
Section: Thoracic Epidural Analgesiamentioning
confidence: 99%
“…The meta-analysis that included four RCTs (n=278 patients) demonstrated that, compared with opioid intravenous PCA, TEA provided superior pain relief at rest and with movement at 12 and 24 hours after surgery, with no significant difference in hospital length of stay (LOS). 40 Of the four RCTs included in the meta-analysis, two RCTs 32 35 are also included in our review. Of note, the meta-analysis did not consider the use of basic analgesics in the included RCTs.…”
Section: Thoracic Epidural Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic intravenous administration of analgesics (as opioids and non-steroidal anti-inflammatory drugs) is effective but associated with potentially harmful side effects, such as respiratory depression, nausea and vomiting, pruritus, gastrointestinal bleeding, and renal failure [13,14]. Epidural analgesia might provide improved pain control, but in the specific setting of open liver surgery, may potentially challenge and have harmful drawbacks as a sympathetic blockade (with hypotension, bradycardia) and intraoperative fluid overload arises and its use might be limited because of the possible perioperative coagulopathy [13,[15][16][17][18]. A peripheral nerve block, such as the paravertebral nerve block (PVB), transversus abdominis plane block (TAP), or quadratus lumborum block (QLB), performed under ultrasound guidance is an emerging alternative that could provide effective analgesia with a potentially low-risk profile after open liver surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized controlled trials have been carried out to compare the effectiveness and safety of PCA to epidural analgesia in patients undergoing open hepatic resection and have reported conflicting results [ 82 , 83 ]. In a systematic review and meta-analysis, Li et al reported that EA was more effective than PCA in controlling postoperative pain in patients undergoing open hepatic resection, with no significant differences in length of hospital stay, complications or transfusion requirements [ 84 ].…”
Section: Postoperative Analgesiamentioning
confidence: 99%